2022
DOI: 10.1016/j.ensci.2022.100392
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and institutional predictors of stroke hospitalization mortality among adults in the United States

Abstract: Introduction Stroke remains a primary source of functional disability and inpatient mortality in the United States (US). Recent evidence reveals declining mortality associated with stroke hospitalizations in the US. However, data updating trends in inpatient mortality is lacking. This study aims to provide a renewed inpatient stroke mortality rate in a national sample and identify common predictors of inpatient stroke mortality. Methods In this cross-sectional study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…[31] Our mortality rate is signi cantly higher than in developed countries, for example, the US, circa 2.1%. [32] It is also relatively high when compared to other developing countries, with the exception of some Caribbean islands (Martinique 22.8%, Barbados 13.1%) and sub-Saharan Africa (22%). [33], [34], [35] Our study showed that hemorrhagic stroke was a predictor of in-hospital mortality, and when classi ed by CT ndings, both IPH and SAH were predictors of in-hospital and three-month mortality.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[31] Our mortality rate is signi cantly higher than in developed countries, for example, the US, circa 2.1%. [32] It is also relatively high when compared to other developing countries, with the exception of some Caribbean islands (Martinique 22.8%, Barbados 13.1%) and sub-Saharan Africa (22%). [33], [34], [35] Our study showed that hemorrhagic stroke was a predictor of in-hospital mortality, and when classi ed by CT ndings, both IPH and SAH were predictors of in-hospital and three-month mortality.…”
Section: Discussionmentioning
confidence: 96%
“…[65] Additionally, data from the US found that in both ischemic and hemorrhagic stroke, there is a higher risk of death with older age. [32] There are, however, more strokes and stroke deaths in women than in men, thought to be largely related to a longer life expectancy for women. In some studies, stroke incidence among women surpasses that of men for those over 80 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was noted in China between 2007 and 2010 5 and in the United States between 2010 and 2017. 6 There are several hypotheses that explain this trend, but it is likely that greater access technology played a role. Regardless of this change, LMICs still bear a greater burden from ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Уровень заболеваемости (инцидентности) у населения КР с 2005 г. по 2022 г. имеет выраженную тенденцию к снижению (темп снижения -10,4% по отношению к 2005 году). Динамика эпидемиологических показателей в ряде стран показала положительную тенденцию к снижению летальности и смертности от инсульта, что явилось результатом качественных изменений в системе оказания специализированной медицинской помощи, внедрения новых методов диагностики и лечения [2,9]. Согласно прогнозам исследователей, в период с 2020 по 2030 год заболеваемость ишемическим инсультом увеличится среди лиц обоего пола, всех возрастных групп, а также в некоторых странах.…”
Section: результаты и их обсуждениеunclassified
“…Согласно прогнозам исследователей, в период с 2020 по 2030 год заболеваемость ишемическим инсультом увеличится среди лиц обоего пола, всех возрастных групп, а также в некоторых странах. Кроме того, страны с низким социо-демографическим индексом должны быть осведомлены о потенциальном увеличении стандартизированной по возрасту смертности и DALY в результате ишемического инсульта [9,10,11].…”
Section: результаты и их обсуждениеunclassified